MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI TARIMENGGUNAKAN MODEL KOOPERATIF TIPE STAD DI KELAS VII.3 SMP NEGERI 10 PADANG - Atikah Tri Nadella; Yuliasma (Universitas Negeri Padang, 2025)
This study aims to improve student learning outcomes in dance learning using the STAD Cooperative Model in class VII.3 of SMP Negeri 10 Padang. The research used Classroom Action Research (CAR) in two cycles, consisting of planning, implementation, observation, and reflection. Data was collected through observation, documentation, and written tests. Data was analyzed using a percentage formula. The research instrument used was written test questions. Learning outcomes using the STAD model showed improved results. The average student learning completion rate in cycle 1 increased to 90 in cycle 2, with a success rate of 48% in cycle 1 and 87% in cycle 2. The results concluded that dance learning using the Student Teams Achievement Division (STAD) model can improve the learning outcomes of class VIII A students at SMP Negeri 10 Padang. This study recommends that future researchers vary the use of the Student Teams Achievement Division (STAD) learning model in the learning process to further improve students' dance learning outcomes.